Proceedings, "WASCOM 2007" : 14th Conference on Waves and Stability in Continuous Media : Baia Samuele, Sicily, Italy ; 30 June - 7 July 2007 - Manganaro, Natale; Monaco, R. (Roberto); Rionero, Salvatore (World Scientific, 2008)
This volume is the fifth in a series of proceedings which started in 1999. The contributions include the latest results on the theory of wave propagation, extended thermodynamics, and the stability of the solutions to partial differential equations.